The Development and Testing of a Positive Psychology-Based Program for Increasing Happiness among Parents of Children with Autism Spectrum Disorder in Thailand - Ananpatiwet, Somdee; Blauw, Jon Nicholas (Scholar: Human Sciences, 2017)
The current research investigated the role of positive psychology in contributing to the development of happiness among parents of children with autism spectrum disorder (ASD). To fulfill the main objectives, this research comprised three studies. Study I employed a qualitative design which used the hermeneutic phenomenological framework in which in-depth interviews were conducted to identify thematic dimensions to inform the development of the Happiness in Parents of Children with ASD Scale (HPCA). Study II involved a quantitative approach in which exploratory factor analysis, reliability analysis, and confirmatory factor analysis were used to develop a psychometrically sound measurement instrument– the HPCA Scale. Tests of validity via both convergent and divergent tests of validity showed that this newly developed scale is valid. Study III employed the nine-component factor structure identified for the HPCA to develop the modified positive psychology-based intervention program and test its effectiveness. The last study investigated the effectiveness of the modified positive psychology-based program via multivariate 2 x 2 mixed-repeated measures design. The results of Study I found three main themes for creating the new survey questionnaire. The results of Study II revealed the final nine-component structure of Happiness in Parents of Children with ASD Scale (HPCA). The findings in Study III indicated that seven of the nine components were significant, namely, hope in the child’s independence, positive acceptance of the child’s disorder, parental self-efficacy, confidence in helping child development, mind-body relaxation, contribution to society, and stress management. Promoting positive family support and resilience were not found to be significantly related to developing happiness among parents. The modified program also had an effect on decreasing depression, one of the components in the DASS-21. Further application of the program that integrates positive psychology should be considered in promoting parental happiness in other areas of child and adolescent disabilities.